Development of Android Based Educational Games as Learning Media on the Concept of Coordination System for Grade XI High School Students - Avina Yustriani; Zulfiani Zulfiani* (Jurnal Pendidikan Sains Indonesia, 2023)
Many students spend time with their smartphones for entertainment, one of which is playing games, and rarely use their smartphones for learning media. This study aims to develop educational game applications, and determine the feasibility and responses of teachers and students to android based educational game applications on the concept of a coordination system. This study uses a developmental research method with a 4D development model consisting of four stages: define, design, develop, and disseminate. The sampling technique is by purposive sampling. The data collection uses a closed questionnaire. Questionnaires are used to assess the feasibility of media by media experts, material experts, teachers and students. Analysis of the data obtained is carried out by quantitative descriptive. In the define stage, the results were obtained from interviews with biology teachers and the distribution of media needs questionnaires to students. In the design stage, the results of the media design (prototype) are obtained. In the develop stage, the results of the media expert validation were 90.67% (very good), while the material expert validation results were 81.25% (very good). Furthermore, a trial was conducted on the teacher and 35 students of class XII high school. The results of the assessment for teachers are 96.88% (very good) and for students are 87.57%. In the disseminate stage, the teacher's response was 98.75% (very good) and the student's response was 83.42% (very good). It is concluded that the educational game-based android application is appropriate to be used as a media for learning biology